The Contribution of Islamic University to Development of Mosque-Based Non-Formal Islamic Education in Lombok Indonesia - Ahmad Amir Aziz; Miftahul Huda (Al-Hayat: Journal of Islamic Education, 2024)
Although much research has been conducted in the context of the role of universities in society, research on the contribution of Islamic higher education in developing mosque-based non-formal education still needs to be explored. This study aims to identify the role of Islamic universities in supporting and strengthening the management of the Taman Pendidikan Al-Qur'an (TPQ) and mosque-based Majelis Taklim. This research uses a qualitative method with a phenomenological approach. Data were collected through interviews with university leaders, lecturers, mosque administrators, and students. Observations and documentation were taken from 5 campuses and 10 mosques in Mataram, Central Lombok, West Lombok, and East Lombok. Data analysis was carried out by organizing, interpreting, and narratively presenting data, then concluding. The study found that Islamic universities have contributed to preparing cadres of Islamic education, strengthening public awareness, conducting management capacity building, and providing religious speakers and campus ambassadors to strengthen TPQ and based-mosque Majelis Taklim. This study introduces a novel model in which Islamic universities and mosques collaborate to combine academic knowledge with community service within the framework of social capital theory. The success of this approach lies in creating a sustainable educational model and driving community transformation through a synergy grounded in Islamic values, transparent management, and the continuous development of human resources. This collaboration enhances religious education's relevance and fosters meaningful societal impact, making it a robust framework for educational and community advancement.